Housing Transactions Data Portal (DOM): Theoretical Aspects and Possibilities for Practical Implementation - Gorlecka-Łabiak, Ewa (Olsztyn Economic Journal, 2024)
This study aims to describe the government’s concept for creating the Housing Transactions Data Portal (DOM), designed to present statistics on transaction prices in the housing market. The Ministry of Development and Technology proposed the portal, which is to be operated by the Insurance Guarantee Fund through an IT system. This is an innovative solution in the national housing market, with a nationwide scope, that will expand the bargaining power of homebuyers (thus aligning with the broader protection of financial consumer services and acting as a tool for safeguarding homebuyers). At the same time, this database will enable public authorities to conduct real-time analyses of the housing market, including assessing the impact of housing support instruments on the market. The considerations in this article focus on analyzing the potential benefits and possible problematic areas related to the implementation of the DOM portal.